ENHANCING CAREER READINESS IN VOCATIONAL EDUCATION: THE ROLE OF PSYCHOMETRIC TEST TRAINING FOR INDONESIAN HIGH SCHOOL STUDENTS - Imroatun Nafia; Siti Juariah (EDUCATIONE, 2025)
The persistent challenge of high unemployment rates among Indonesian vocational high school (SMK) graduates highlights the need for holistic approaches to career readiness, extending beyond technical instruction to include psychological preparation for recruitment and selection processes. This study aims to explore the perceptions of grade XI students at SMK Garuda Nusantara regarding psychological test training (specifically the TIU 5 General Intelligence Test) and its impact on their career readiness. Employing a qualitative case study design, data were collected through purposive sampling of students who participated in open-ended questionnaires, in-depth interviews, and classroom observations, and analyzed thematically using NVivo 12. The findings reveal that the majority of students perceive themselves as ready to transition to the workforce or higher education, with both internal factors (motivation, self-confidence) and external factors (internships, parental and teacher support, and structured psychometric practice) playing significant roles. Psychometric test training was found to enhance students’ self-awareness, self-efficacy, and confidence, while reducing anxiety toward recruitment assessments. Students regarded these exercises as directly relevant to their future career and educational pathways. The study concludes that integrating systematic psychological test practice within vocational guidance programs not only addresses a critical gap in the Indonesian context but also fosters greater adaptability and success in school-to-work transitions. This research underscores the importance of reflective, experiential, and motivational interventions in vocational education and recommends expanding psychometric test training to improve employability outcomes for SMK graduates.